Determinants of Green Organizational Citizenship Behavior: An Empirical Study on Employees’ Environmental Motivation - Joshi, Surendra Prasad; Dahal, Rewan Kumar; Ghimire, Binod; Subedi, Sugam (NCC Journal, 2025)
It is the modern work system that divides and rules the creative people who think of consumption and contributions, and such people need to be changed. The study observed the factors that are affecting the green organizational citizenship behaviour (GOCB) of the employees working in the private sector of Nepal. For this study, a positivist research approach was adopted along with descriptive and causal research designs. The non-probability sample technique was used to select a sample of 384 respondents through purposive and random sampling techniques. The results indicated that green skills, green employee empowerment, green values, and green knowledge-sharing behaviour positively and significantly influence green organizational citizenship behaviour. The analysis of multiple regression shows that these factors together are accountable for a huge part of the variance in GOCB, thereby highlighting their pivotal position in promoting sustainable practices across the companies. The study also proposes that the importance of strategically nurturing the long-term survival of human beings and all green skills through empowerment, values, and co-existence knowledge-sharing behaviour of humans to employees, leading to environmental leadership for the long run, thus sustainable economic growth.